Anti-Pancasila Offence: Protection of National Security or Threat to Freedom of Speech - Vidya Prahassacitta (Kosmik Hukum, 2024)
The research discusses anti-Pancasila offenses in relation to national security and freedom of speech. Focus on the distribution of Communism, Marxism, and Leninism. Three research questions are the harm of spreading anti-Pancasila, the implementation of these offenses in court verdicts, and the formulation of these offenses in the new Penal Code. The research is document research using statutory and case approaches. Harm principles are used to analyze the research problems. Research results show that the distribution of Communism, Marxism, and Leninism has harmed other people, democratic states, and citizen exercising their fundamental rights. The implementation and formulation of these offenses in the new Penal Code also need help. Consequently, this offense cannot fulfill its objection to protecting national security interests; on the contrary, it becomes a threat to freedom of speech in the public sphere.Keywords: Anti-Pancasila, national security, freedom of speech